Quid si adeam ad fores atque occentem? (Pl. Curc. 145): alusión y transformación en el motivo del paraclausithyron (Argos, 2025)
Among all the metatheatrical techniques examined by Timothy Moore, the technique which molds the actors' relationship with their audience by means of the allusions to Rome is particularly interesting. The plays of Plautus are set in Greece and the characters repeatedly call atention to their greekness. Plautus plays are, in the words of Gruen, "our chief document for the cultural convergence of Hellas and Rome" and the earliest literary source for the reaction to the Greek world, a defining feature of Roman culture. Confrontation and interpenetration of two cultures form the principal motif of the plays. In order to illustrate the dynamics of interchange and transformation, this paper analyzes in Curculio the scene of paraclausithyron in accordance with the metatheatrical technique of the allusions to Rome.
Keywords: allusion; Plautus; transformation; metatheatre; paraclausithyron